rpoE, the gene encoding the second heat-shock sigma factor, sigma E, in Escherichia coli. - Rouvière, P E (1995)
In Escherichia coli, the heat shock response is under the control of two alternative sigma factors: sigma 32 and sigma E. The sigma 32-regulated response is well understood, whereas little is known about that of sigma E, except that it responds to extracytoplasmic immature outer membrane proteins. To further understand this response, we located the rpoE gene at 55.5' and analyzed the role of sigma E. sigma E is required at high temperature, and controls the transcription of at least 10 genes. Some of these might contribute to the integrity of the cell since delta rpoE cells are more sensitive to SDS plus EDTA and crystal violet. sigma E controls its own transcription from a sigma E-dependent promoter, indicating that rpoE transcription plays a role in the regulation of E sigma E activity. Indeed, under steady-state conditions, the transcription from this promoter mirrors the levels of E sigma E activity in the cell. However, it is unlikely that the rapid increase in E sigma E activity following induction can be accounted for solely by increased transcription of rpoE. Based upon homology arguments, we suggest that a gene encoding a negative regulator of sigma E activity is located immediately downstream of rpoE and may function as the target of the E sigma E inducing signal.